Association between healthy eating index-2015 and abdominal aortic calcification among US Adults - Jia, Jundi; Zhang, Jie; Ma, Dan; Zhang, Zihao; Zhao, Lin; Wang, Tongxin; Xu, Hao (Frontiers in Nutrition, 2023)
Aims To evaluate the relationship of the healthy eating index-2015 (HEI-2015) with abdominal aortic calcification (AAC) in US adults. Methods We conducted a cross-sectional study with data extracted from the National Health and Nutrition Examination Survey (NHANES). AAC score was measured using the scoring system of Kauppila (AAC-24) and Schousboe (AAC-8). HEI-2015, which was used for evaluating compliance with Dietary Guidelines for Americans (DGA), was calculated through two rounds of 24-h recall interviews. HEI-2015 was categorized as inadequate (<50), average (50 70), and optimal (≥70) groups for analysis, while the AAC-24 score was grouped by whether the score was >0. Weighted multiple regression analyses were conducted to estimate the association of HEI-2015 with AAC score and the presence of AAC. Moreover, smooth curve fittings, based on a generalized additive model (GAM), were applied to evaluate a possible non-linear relationship. Sensitivity analysis and subgroup analysis were performed to provide more supporting information. Results A total of 2,704 participants were included in the study (mean age, 57.61 ± 11.40 years; 51.78% were women). The mean score of HEI-2015 was 56.09 ± 13.40 (41.33 ± 6.28, 59.44 ± 5.54, and 76.90 ± 5.37 for inadequate, average, and optimal groups, respectively). After adjusting for covariates, higher HEI-2015 was associated with decreased AAC score (AAC-24: β = −0.121, 95% CI: −0.214, −0.028, P = 0.010; AAC-8: β= −0.054, 95% CI: −0.088, −0.019, P = 0.003) and lower risk of AAC (OR = 0.921, 95% CI: 0.855, 0.993, P = 0.031). Among the components of HEI-2015, a higher intake of fruits, greens, and beans was associated with a lower AAC score. Subgroup analysis showed that an inverse association of HEI-2015 with AAC score existed among different groups. Conclusion The study presented that higher HEI-2015 was related to a lower AAC score and decreased risk of having AAC, indicating that greater compliance with 2015–2020 DGA, assessed by HEI-2015, might be beneficial for preventing vascular calcification and CVD among US adults.